1995
DOI: 10.1161/01.hyp.25.3.350
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Regulation of Renal α 2B -Adrenergic Receptor mRNA Levels

Abstract: Androgens regulate blood pressure and renal alpha 2-adrenergic receptors in a parallel fashion in the spontaneously hypertensive rat (SHR). The present studies investigated whether this regulation of renal alpha 2B-adrenergic receptors occurs at the mRNA level. Male and female SHR were gonadectomized at 4 weeks of age. The gonadectomized rats were implanted with or without testosterone propionate. Sham-gonadectomized rats served as controls. Total kidney RNA was purified, and alpha 2B-adrenergic receptor mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Although the precise mechanism underlying the male-female differences remains to be elucidated, sex hormones are probably involved. Indeed, testosterone stimulates the expression of a2B-adrenoceptors in spontaneously hypertensive rats [27] and is required for full expression of the receptor in salt-induced hypertension in male Sabra rats [28].…”
Section: Alcohol Intake Menopausementioning
confidence: 99%
“…Although the precise mechanism underlying the male-female differences remains to be elucidated, sex hormones are probably involved. Indeed, testosterone stimulates the expression of a2B-adrenoceptors in spontaneously hypertensive rats [27] and is required for full expression of the receptor in salt-induced hypertension in male Sabra rats [28].…”
Section: Alcohol Intake Menopausementioning
confidence: 99%
“…Also androgens may aid the onset of hypertension in spontaneously hypertensive rats, through the increased activity of the tyrosinehydroxylase enzyme (Kumai et al, 1995), which primarily increases the levels of norepinephrine (NE) in the blood. Gong et al (1995) found that androgens can regulate the blood pressure in spontaneously hypertensive rats, and showed that the treatment with testosterone (T) elevates the number of α 2 -adrenergic receptors in the whole kidney of females and in castrated males, compared with controls.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ␣ 2B -adrenoceptor densities were markedly increased by the high salt diet. These high levels, which appear to be the consequence of an overexpression of the encoding gene, have also been observed in SHR rats (Gong et al, 1994(Gong et al, , 1995. However, the ␣ 2A -adrenoceptor mRNA was clearly present in kidneys of intact SBH rats under both normal and high salt diet.…”
Section: Discussionmentioning
confidence: 53%
“…In the kidney of the normotensive rat, ␣ 2A -and ␣ 2B -adrenoceptor subtypes have been characterized by binding studies (Uhlen and Wikberg, 1991). In SHR rats, testosterone regulates renal ␣ 2B -adrenoceptor density at the mRNA level (Gong et al, 1995). From this study, it has been postulated that the effects of testosterone on renal ␣ 2B -adrenoceptor mRNA and ␣ 2B -adrenoceptor density are tightly associated with blood pressure and probably responsible for the hypertension in SHR rats.…”
mentioning
confidence: 91%